Core Decompression with Local Administration of Zoledronate and Enriched Bone Marrow Mononuclear Cells for Treatment of Non‐Traumatic Osteonecrosis of Femoral Head. Issue 6 (18th October 2021) - Ma, Hai‐yang; Ma, Ning; Liu, Yu‐feng; Wan, Yi‐qun; Liu, Gui‐qi; Liu, Guang‐bo; Meng, Hao‐ye; Li, Huo; Wang, Xin; Li, Chun‐bao; Peng, Jiang
Abstract : Objective: To investigate the efficacy and safety of core decompression (CD) with local administration of zoledronate and enriched bone marrow mononuclear cells (BMMCS) for the treatment of non‐traumatic osteonecrosis of femoral head (ONFH). Methods: A total of 17 patients (30 hips) diagnosed with stage II and III ONFH according to the 2019 revised Association for Research on Osseous Circulation (ARCO) staging criteria from 2012 to 2014 were retrospectively reviewed. The patients received the following therapy: the BMMCs and zoledronate were injected into the necrotic zone, respectively, along with CD. The mean age of the patients was 36.8 years; 14 were men and three were women. All patients included had non‐traumatic ONFH and a minimum follow‐up of 5 years, which ended when total hip arthroplasty (THA) was performed. Imaging modalities, including plain radiography, computed tomography (CT), and magnetic resonance imaging (MRI) were taken pre‐ and postoperatively. Harris hip score (HHS) was used to evaluate the functional outcomes of femoral head necrosis. Kaplan–Meier analysis was adopted to determine the probability of survivorship with THA as the end point in this series of patients. The correlation between radiological progression or THA and related risk factors were further analyzed. All complications were recorded. Results: With THA as the follow‐up endpoint, All patients were followed up for an average of 69.1 ± 20.5 months (range, 18–95 months). Preoperative imaging found six hips (20%) at ARCO stage II, 14 hips (46.7%) at stage IIIA, 10 hips (33.3%) at stage IIIB. Fourteen hips (46.7%) shown progression radiologically, while six hips (20%) underwent TKA among these patients with hip preservation. The cumulative survival was 80% (95% CI, 0.608–905) at 5 years with THA as the end point. HHS improved from 63.3 ± 8.7 preoperatively to 74.6 ± 20.6 postoperatively ( P = 0.000). Radiological progression was found to be associated with ARCO stage, Japanese Investigation Committee (JIC) type, and corticosteroid exposure ( P = 0.047; P = 0.012; P = 0.031). However, no correlation was found between conversion to THA and the known risk factors. No major complication was reported, with only four patients complaining about general weakness and muscle soreness, and all disappeared within 2–3 days. Conclusions: The novel treatment modality could relieve pain, delay the progression of collapse, which might be an effective and safe method for hip preservation of early and mid‐term ONFH. However, the effect of this method may be related to ARCO stage, JIC type, and corticosteroid exposure. Abstract : The diagram of the procedure step by step. A: Extraction of BMMCs; B: Extraction of the vein blood; C: Stratified mixed sample after centrifugation; D: Administration of the zoledronate and enriched BMMCs. Yellow syringe: zoledronate. Red syringe: enriched BMMCs.